Dimensionality of Communities’ Belief Attitude toward Tourism Development: The Case of Bario. - Abang Azlan, Mohamad; Alvin Yeo, W.; Songan, Peter; Lo, May Chiun (2011)
Rural tourism is becoming increasingly important to the Malaysian economy and tourism product offering. Rural tourism enables tourists to reunite with nature and the culture of the destinations, and that it contributes to the economic and social recovery of the rural areas, as well as to the conservation of the environment and the spreading of local cultures. Nonetheless, development projects are often designed and implemented in which indigenous people have minimal voice in policy and management of it. Tourism which simply transplants urban investment and enterprises to a rural setting does little to improve communities' incomes. As a result, many indigenous people rightly feel that tourism industry has a poor track record, in disregarding their legitimate interests and rights, and profiting from their cultural knowledge and heritage. The present study in the paper involved looking at validating the dimensionality of the four tourism impact namely, economics, environment, social and cultural impact as perceived by local communities. Data was gathered through a survey using a structured questionnaire and administered to the community members residing at Bario. A series of tests such as factor analysis, correlation, and reliability analysis was conducted to confirm that the instrument is valid (content, construct, convergent, discriminant and nomological) as well as reliable. Implications regarding the value of conducting validity and reliability test for practitioners and researchers are discussed.